Pengaruh Umur Perusahaan, Ukuran Perusahaan, Leverage, Ukuran Dewan Komisaris, dan Kepemilikan Saham Publik Terhadap Pengungkapan Corporate Social Responsibility (CSR)(Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Aprilliani, Dhiya'ul Azizah; , Eny Kusumawati SE, Akt, CA (2017)
Corporate social responsibility is a form liability company on social and environmnet around where teh companies are. The CSR is a process where the company revealed information related to the activities of the company and uts effect on the social conditions and the comunity.The aim of this research is to analyze the influence of firm age, firm size, leverage, size of board of commissioners, and public ownership on the corporate social responsibility (CSR). The measurement of corporate social responsibility based on the global reporting intiatives disclosure index (GRI) 2013 as seen from the company's annual report. The population of this research is manufacture companies listed in Indonesia Stock Exchange (IDK) 2013-2015. Research sampling used purposive sampling technique and found 46 companies, with 3 years of observation. So, the total sample studied was 138. The collected data was analyzed using classic assumption test then do hypothesis test. Testing the hypotesis in this study using multiple regression analysis with t-test, f, and coefficient of determination. The result indicate that size of board of commissioners have a significant influence on the corporate social responsibility (CSR). Meanwhile, firm age, firm size, leverage, and public ownership don't have significant influence on the corporate social responsibility (CSR).